Borrelia valaisiana resist complement-mediated killing independently of the recruitment of immune regulators and inactivation of complement components - Schwab, Jasmin Sabrina; Hammerschmidt, Claudia; Richter, Dania; Skerka, Christine; Matuschka, Franz-Rainer; Wallich, Reinhard; Zipfel, Peter F.; Kraiczy, Peter (PLOS ONE, 2013)
Spirochetes belonging to the Borrelia (B.) burgdorferi sensu lato complex differ in their resistance to complement-mediated killing, particularly in regard to human serum. In the present study, we elucidate the serum and complement susceptibility of B. valaisiana, a genospecies with the potential to cause Lyme disease in Europe as well as in Asia. Among the investigated isolates, growth of ZWU3 Ny3 was not affected while growth of VS116 and Bv9 was strongly inhibited in the presence of 50% human serum. Analyzing complement activation, complement components C3, C4 and C6 were deposited on the surface of isolates VS116 and Bv9, and similarly the membrane attack complex was formed on their surface. In contrast, no surface-deposited components and no aberrations in cell morphology were detected for serum-resistant ZWU3 Ny3. While further investigating the protective role of bound complement regulators in mediating complement resistance, we discovered that none of the B. valaisiana isolates analyzed bound complement regulators Factor H, Factor H-like protein 1, C4b binding protein or C1 esterase inhibitor. In addition, B. valaisiana also lacked intrinsic proteolytic activity to degrade complement components C3, C3b, C4, C4b, and C5. Taken together, these findings suggest that certain B. valaisiana isolates differ in their capability to resist complement-mediating killing by human serum. The molecular mechanism utilized by B. valaisiana to inhibit bacteriolysis appears not to involve binding of the key host complement regulators of the alternative, classical, and lectin pathways as already known for serum-resistant Lyme disease or relapsing fever borreliae.